2011
DOI: 10.5600/mmrr.001.04.a05
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance in the Use of Cardiovascular Medications in the Medicare Part D Population

Abstract: OBJECTIVES:(1) to assess non-compliance among Medicare Part D recipients for the cardiovascular medication classes; (2) to identify the probability of noncompliance for each medication class when controlling for the potential risk factors of age, gender, race/ethnic origin, census region, disease burden, dual eligibility enrollment status, Part D plan status, relative out-of-pocket (OOP) non-class costs, and relative OOP daily class costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…We report two primary findings. First, consistent with existing literature, we found that nonwhite patients were more likely to be nonadherent than white patients 45,46. Second, we determined that factors associated with nonadherence did not differ as a function of patients’ race.…”
Section: Discussionsupporting
confidence: 83%
“…We report two primary findings. First, consistent with existing literature, we found that nonwhite patients were more likely to be nonadherent than white patients 45,46. Second, we determined that factors associated with nonadherence did not differ as a function of patients’ race.…”
Section: Discussionsupporting
confidence: 83%
“…The implementation of the Medicare Part D program has been associated with up to a 13.5% improvement in antihypertensive adherence among beneficiaries (8). However, antihypertensive nonadherence continues to pose a threat to this population's health, especially among certain demographic groups (9). This study used the most currently available data to describe antihypertensive nonadherence among Medicare Part D beneficiaries, and assessed nonadherence stratified by multiple factors, including antihypertensive class and beneficiaries' state and county of residence, type of prescription drug plan, and treatment and demographic characteristics, to help identify and inform targeted interventions among the groups and regions most at risk.…”
Section: Introductionmentioning
confidence: 99%
“…OTC medicine is usually considered safe to use and available for self-medication [ 1 , 3 ]. Even though OTC medicines are comparably safe and mild in effects, the misuse of medicine, which was proven not rare in the UK, can still lead to severe consequences such as addiction and fatality [ 4 , 5 , 6 ]. This situation has raised concern since medicines such as OTC codeine, the most widely used opioid medicine, is very likely to cause harm [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%